1996
DOI: 10.1128/jvi.70.10.7233-7235.1996
|View full text |Cite
|
Sign up to set email alerts
|

CpG methylation directly inhibits binding of the human papillomavirus type 16 E2 protein to specific DNA sequences

Abstract: CpG methylation of the human papillomavirus upstream regulatory region has previously been shown to reduce virus promoter activity. Here, we demonstrate that methylation of the CpG dinucleotides contained within the binding site of the human papillomavirus type 16 E2 protein has a direct effect on the interaction of this protein with DNA. Methylation of both CpG dinucleotides within the E2 site abolishes the binding of E2. * Corresponding author. Phone: 44-117-928-7439. Fax: 44-117-928-8274. FIG. 1. Oligonucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 91 publications
(46 citation statements)
references
References 26 publications
1
42
0
3
Order By: Relevance
“…In this regard, methylation of CpG dinucleotides within the E2BSs in the HPV URR has been demonstrated to alter binding affinity of the E2 protein, to activate the p97 promoter, and, consequently, to enhance E6 and E7 transcription in the presence of E2. [23][24][25] This role of methylation is supported by in vitro models demonstrating a hyperactivation of the p97 promoter at the time of E2 binding to the methylated high-affinity E2BS1 24 and parallel disruption of promoter inhibition by impaired binding of E2 to methylated low-affinity E2BS3 and E2BS4 ( Fig. 1B).…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…In this regard, methylation of CpG dinucleotides within the E2BSs in the HPV URR has been demonstrated to alter binding affinity of the E2 protein, to activate the p97 promoter, and, consequently, to enhance E6 and E7 transcription in the presence of E2. [23][24][25] This role of methylation is supported by in vitro models demonstrating a hyperactivation of the p97 promoter at the time of E2 binding to the methylated high-affinity E2BS1 24 and parallel disruption of promoter inhibition by impaired binding of E2 to methylated low-affinity E2BS3 and E2BS4 ( Fig. 1B).…”
Section: Introductionmentioning
confidence: 59%
“…1B). 23 We hypothesized that CpG methylation of the activating E2BS1 and repressive E2BS3 and E2BS4 in the . Schematic illustration of the human papillomavirus (HPV) upstream regulatory region with its E2-binding sites (E2BSs) and CpG dinucleotides with regard to (A) the regulation of E6/E7 expression by binding of E2 to E2BSs and (B) the consequence of methylation.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, within the promoter region of HPV16, we observed increased methylation at E2BS3 as well as a tendency for methylation within the E2BS4 of the xenograft, which could possibly reduce the ability of the E2 to repress transcription of E6 and E7 genes. 50,51 Despite increased methylation at these E2BS sites, the level of E7 mRNA expression was rather modest in the xenograft.…”
Section: Discussionmentioning
confidence: 97%
“…40 The data reported in this study suggest that methylation of the proximal E2 binding sites (E2BS3 and 4) in addition to methylation of the E2BS1 might contribute to the transformationassociated activation of the URR in the episomal HPV16 genome most likely due to loss of binding of E2 to the repressive low affinity binding sites E2BS3 and 4. 29,30 If the HPV16 genome becomes integrated and E2 ORF is disrupted or lost, methylation of E2BSs more likely does not bring any selective advantages for the cell clones in the absence of intact E2.…”
Section: Discussionmentioning
confidence: 99%
“…28 Previous reports demonstrated that the capacity of the E2 protein to bind the consensus E2BS sequence in vitro is blocked by methylation of CpG dinucleotides. 29 These data suggested that methylation of E2BSs may interfere with the regulatory functions of E2 upon binding to these sites and potentially could activate transcription of the downstream early genes including E6 and E7. 30 The first evidence that DNA methylation is an important regulatory mechanism in modulating HPV expression came from in vitro studies demonstrating that the transcriptional activity of the HPV18 URR can be altered by DNA methylation.…”
Section: What's New?mentioning
confidence: 93%